2019
DOI: 10.18203/2394-6040.ijcmph20195050
|View full text |Cite
|
Sign up to set email alerts
|

Hand washing practices amongst mothers of under-fives in an urban slum

Abstract: Background: Hand washing with soap is a cost-effective tool of disease prevention, but most of the time it is overlooked. Use of contaminated hands enhances transmission of germs into body causing ill-health. Mothers clean, prepare, serve and feed the food. If this is coupled with poor knowledge and practice of hand washing it increases risk to spread of diseases to self, other family members especially to under-fives. Present study was conducted to address this issue being a critical factor in disease prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
2
1
Order By: Relevance
“…Similar observations were reported (89-100%) in an urban slum in Latur, Maharashtra (Quazi et al 2019), but the frequency was that the same practice was reported to be lower in Kolkata-based (66-70%) and in Ethiopia-based (62-78%)-based studies (Ali et al 2018;Melese et al 2019). In another post-defaecation handwashing study, Mohd & Malik (2017) reported frequencies to be 93.8% in Bangalore city, which is similar to our observations; however, washing hands after cleaning children post defaecation was reported to be considerably low (33%).…”
Section: Hygiene Practices and Sanitationsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar observations were reported (89-100%) in an urban slum in Latur, Maharashtra (Quazi et al 2019), but the frequency was that the same practice was reported to be lower in Kolkata-based (66-70%) and in Ethiopia-based (62-78%)-based studies (Ali et al 2018;Melese et al 2019). In another post-defaecation handwashing study, Mohd & Malik (2017) reported frequencies to be 93.8% in Bangalore city, which is similar to our observations; however, washing hands after cleaning children post defaecation was reported to be considerably low (33%).…”
Section: Hygiene Practices and Sanitationsupporting
confidence: 89%
“…In another post-defaecation handwashing study, Mohd & Malik (2017) reported frequencies to be 93.8% in Bangalore city, which is similar to our observations; however, washing hands after cleaning children post defaecation was reported to be considerably low (33%). In this study, the rate of handwashing before cooking food and eating was found to be between 47.3 and 56.3%, respectively, which is slightly higher (40-43%) than that in a Kolkata-based study (Ali et al 2018), while the study based in Latur showed a higher frequency at 70-98% (Quazi et al 2019).…”
Section: Hygiene Practices and Sanitationcontrasting
confidence: 59%
See 1 more Smart Citation
“…These findings were also supported by some other studies. [ 30 31 ]…”
Section: Discussionmentioning
confidence: 99%